2013
DOI: 10.1186/1755-8166-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a pericentromeric BAC clone set aimed at improving diagnosis and phenotype prediction of supernumerary marker chromosomes

Abstract: BackgroundSmall supernumerary marker chromosomes (sSMCs) are additional, structurally abnormal chromosomes, generally smaller than chromosome 20 of the same metaphase spread. Due to their small size, they are difficult to characterize by conventional cytogenetics alone. In regard to their clinical effects, sSMCs are a heterogeneous group: in particular, sSMCs containing pericentromeric euchromatin are likely to be associated with abnormal outcomes, although exceptions have been reported. To improve characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…No relevant cross-hybridizations or background could be observed. The idea for how to establish this kind of probeset was previously stated in a comment for a paper published by Castronovo and colleagues in 2013 [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No relevant cross-hybridizations or background could be observed. The idea for how to establish this kind of probeset was previously stated in a comment for a paper published by Castronovo and colleagues in 2013 [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…sSMCs of different sizes present in the same patient [ 14 , 24 ], previously, we established already a probe sets called pericentric-ladder-FISH (PCL-FISH) with a resolution of ~10 Mbps [ 25 ]. Also two similar probe sets were published before in 2007 and 2013 [ 19 , 26 ]. However, a probe set for the pericentric region for narrowing down the dosage insensitive regions of all human chromosome arms was not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies have shown this can occur in an acquired fashion in hematopoietic and solid organ malignancies . Unfortunately, these LOH or copy number‐neutral changes could not be detectable by current FISH platforms, despite using a BAC clone probe (RP11‐572M14, chr3: 10,011,785‐10,180,797) that covers the entire sequence of VHL gene (VHL, chr3:10,141,008‐10,153,670) . Further molecular analysis, particularly by high‐resolution single‐nucleotide polymorphism microarrays, may serve to identify an even higher percentage of alterations in 3p chromosomal regions in future studies …”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72] Unfortunately, these LOH or copy number-neutral changes could not be detectable by current FISH platforms, despite using a BAC clone probe (RP11-572M14, chr3: 10,011,785-10,180,797) that covers the entire sequence of VHL gene (VHL, chr3:10,141,008-10,153,670). 16,17,25,26,69,73 Further molecular analysis, particularly by high-resolution single-nucleotide polymorphism microarrays, may serve to identify an even higher percentage of alterations in 3p chromosomal regions in future studies. 8,16,17,26,68 RCC with sarcomatoid features is an aggressive, heterogeneous subset of tumors that frequently present at a high clinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…The euchromatic material in sSMC can be detected by a microarray analysis. A set of pericentric core probes for each arm of human chromosomes has been validated for characterizing unambiguously the chromosomal origin of sSMC and the level of mosaicism (Castronovo et al, 2013 ).…”
Section: Cell Based Genetic Diagnosis By Fishmentioning
confidence: 99%